An Analysis on Employees Satisfaction towards Human Resource Management Practices: Exploring the Impact of Human Resource Management Practices on Employee Satisfaction (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The most esteemed resource of an association is its human resource. Human resource improvement and human resource management are the two key regions considered by the management. The human resource advancement present with a thorough system and strategies for the improvement of HR in an association. Both closed ended, likert scale and open ended questions based on market qualities as well as variables which effect employees' satisfaction towards human resource management practices This is to produce methodical data about HR for labor arranging, position and advancement. The human resource improvement upgrades the possibilities of an association in the enlistment, hold and inspires the employees. HR Practices are actually linked with the management of human resources, tasks needed for staffing the group and sustaining higher employee efficiency. For this thesis we used Sample size of 400 employees, which include forty of females' i.e. 160 females as well as sixty of males i.e. 240 men. The current condition in Organization is favorable yet it ought not to forget that business climate is dynamic, so dynamic human resource is needed to manage danger and uncertainties.